2021
DOI: 10.24114/jpf.v10i2.29067
|View full text |Cite
|
Sign up to set email alerts
|

Self Regulated Learning Oriented Physics Module: Design, and Validity

Abstract: The absence of a Mathematical Physics module that follows the characteristics of Mathematics Physics learning achievement for Physics Education students is the focus of attention in this development research. The purpose of this research is to develop a module of Mathematics Physics oriented to Self Regulated Learning. This module is intended explicitly for Physics Education students as a provision in studying advanced Physics courses. This type of research is research and development (R&D), which follows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…Marisda (2021) also carried out the design and validity of the mathematical physics module with a 4D model and found that the module on systems of linear equations and matrices was categorized as very suitable for use, with a score of 80.5. The indicator with the highest score from expert validators is adaptive (90), and the lowest score is self-contained (70) [13].…”
Section: Figure 3 Results Of Module Validity Assessment By Expert Val...mentioning
confidence: 99%
See 3 more Smart Citations
“…Marisda (2021) also carried out the design and validity of the mathematical physics module with a 4D model and found that the module on systems of linear equations and matrices was categorized as very suitable for use, with a score of 80.5. The indicator with the highest score from expert validators is adaptive (90), and the lowest score is self-contained (70) [13].…”
Section: Figure 3 Results Of Module Validity Assessment By Expert Val...mentioning
confidence: 99%
“…The research subjects consisted of expert validators (material, media, and tafsir experts), mathematical physics lecturers, department heads, and the Physics Education Department students who program mathematical physics. This research procedure is guided by the Thiagarajan or 4D research and development stages, namely defining, designing, developing, and disseminating [13]. The details of the research stages can be explained in Table 1 below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seperti Bahasa, pola, dan sifat kelengkapan lainnya yang terdapat dalam modul ini diatur sehingga ia seolah-olah merupakan "bahasa pengajar" atau bahasa pendidik yang sedang memberikan pengajaran kepada peserta didik. Maka oleh sebab itu modul sering disebut bahan instruksional mandiri (Yanti, et al, 2016), karena pendidik tidak secara langsung memberi pelajaran atau mengajarkan sesuatu kepada peserta didik dengan tatap muka, tetapi cukup dengan modul (Marisda, et al, 2021).…”
Section: Pendahuluanunclassified